Locating Academic NGOs in the Knowledge Production Landscape - Onta, Pratyoush (Dhaulagiri Journal of Sociology and Anthropology, 2012)
Academic non-governmental organizations (NGOs) are already one of the most important institutional sites of knowledge production in the countries of the global South. This article defines academic NGOs as those NGOs which produce not only documentation but also academically engaging articles, reports, edited volumes, bibliographies, journals and monographs. It argues that their growth in the recent decades has taken place amidst the mammoth growth in the number of NGOs in general for structural and personal reasons. A case study from Nepal is provided to illustrate, both at the level of procedures and at the level of outcomes, the kinds of contributions academic NGOs have made to the knowledge enterprise. The article ends by suggesting that the links between editorial control over what academic NGOs produce and the funding they receive are more complex than is usually assumed, and that the issue of their accountability needs to be rendered in a multiple-constituency model similar to that at work in conventional universities. DOI: http://dx.doi.org/10.3126/dsaj.v5i0.6356 Dhaulagiri Journal of Sociology and Anthropology Vol. 5, 2011: 49-80